E0282 Effect of comprehensive intervention on Anxiety and depressive symptoms in Patients after ACS. (17th November 2010) - Guanghui, Liu; Xianzheng, Wu; Wenlin, Ma; Lijie, Su; Dayi, Hu
Abstract : Objective: To evaluate the effect of comprehensive intervention to the prognosis of depressive and/or anxiety symptoms in future. To provide a reasonable and reliable intervention instrument to treat ACS patients. Methods: To select acute coronary syndrome with anxious and/or depressive symptoms patients 268 examples, all patients were divided into the intervention group 134 examples and the control group 134 examples. On the base of conventional therapy, Patients of intervention group received comprehensive intervention (health education, exercise, psychological relaxation et al ). Before the intervention and after follow-up test the HADS, to follow up with the patients to observe the dynamic change of emotion. The state of anxiety and depression in all patients were analysed according to psychological test scale. Results: 1. Total 256 example patient include the intervention group (n=130) and the control group (n=126), after giving the treatment has carried on at least two times evaluation. Because loses the revisit 6 examples, died 4 examples, uncompliant patients 6 examples, completed finally experiments 240 examples. 2. Comparing two group's emotion in the two group patients respectively at baseline and after intervention. The HADS scores carried on the difference examination separately: Before the comprehensive intervention, the intervention group's HAD-a, HAD-d, HAD-t are 8.92±3.72, 8.73±3.41, 17.68±3.72 respectively, the control group's scores are 8.67±3.13, 8.52±3.06, 17.47±3.27 respectively, p>0.05; After intervention, for the invention group, HAD-a, HAD-d, HAD-t are 5.82±1.41, 6.84±1.86, 11.93±1.59; The control group's are 6.76±1.31, 7.28±1.58, 13.62±1.36 respectively, p<0.05. Conclusions: For the intervention group patients, comprehensive intervention (Coronary heart disease treatment, Health education, psychological counseling, Relaxation training, taking exercise et al ) may obviously alleviate the anxiety and/or depressive symptoms in ACS patients, it is useful to the prognosis improvement of QOL. 2. On the basis of medication for ACS, for the control group patients, the anxiety and/or depressive symptom has been alleviated to some extent.